Cellular uptake of three different nanoparticles in an inflammatory arthritis scenario versus normal conditions - Lima, Ana Cláudia Fernandes (2021)
Nanoparticles (NPs) have wide potential applications in the biomedical field. To promote targeted and controlled delivery of encapsulated drugs, it is fundamentally important to understand the factors regulating NP uptake by different cells. Thus, the goal of the present study is to assess the internalization rates of different NPs under normal and proinflammatory states in primary human articular chondrocytes (hACs), human umbilical vein endothelial cells (EA), and human monocytes (THP-1). Here, we compared chitosan–hyaluronic acid (Ch-HA) polymeric NPs, methoxypolyethylene glycol amine–glutathione–palmitic acid (mPEG-GSHn-PA) micelles, and cholesterol/L-α-phosphatidylcholine/DSPE-PEG-Mal (Chol/EPC/DSPE-PEG-Mal) unilamellar liposomes (LUVs). Our results reveal the importance of surface charge and chemistry in determining the levels of NP internalization. Under normal conditions, the cellular uptake was ≈30% for Ch-HA NPs and ≈100% for mPEG-GSHn-PA micelles and Chol/EPC/DSPE-PEG-Mal LUVs. A proinflammatory cell state promoted a higher uptake of the Ch-HA NPs by EA cells (93% after 24 h). Since the therapeutic efficacy of the NP-loaded cargo is dependent on trafficking routes after cellular internalization, we tested their internalization pathways. Accordingly, caveolae-mediated endocytosis or energy-independent non-endocytic pathways, which circumvent lysosomal degradation, were accomplished in hACs and EA by LUVs and in M1 polarized macrophages by micelles. The present outcomes highlight the importance of considering cellular uptake and internalization pathways by the target cell when designing functional NPs for therapeutic applications.